Integrative Proteome and Acetylome Analyses of Murine Responses to Cryptococcus neoformans Infection - Li, Hailong; Li, Yanjian; Sun, Tianshu; Du, Wei; Zhang, Zhijie; Li, Dancheng; Ding, Chen (Frontiers in Microbiology, 2020)
Cryptococcus neoformans is a causative agent for pulmonary infection and meningoencephalitis. Understanding the host’s response to C. neoformans infection is critical for developing effective treatment. Even though some have elucidated the host response at the transcriptome level, little is known about how it modulates its defense machinery through the proteome mechanism or how protein posttranslational modification responds to the infection. In this work, we employed a murine infection model and mass spectrometry to systematically determine the proteome and acetylome statuses of lungs and brains in the early stage of infection. To extensively analyze the host response, we integrated the proteome data to the transcriptome results. Critical genes, including genes involved in phagosome, lysosome and platelet activation are significantly altered in protein and gene expression during infection. In the acetylome analysis, we demonstrated that lung and brain tissues differentially regulate protein acetylation during infection. The three primary groups of proteins altered in acetylation status are histones, proteins involved in glucose and fatty acid metabolism, and proteins from the immune system. These analyses provide an integrative regulation network of the host responding to C. neoformans and shed new light on understanding the host’s regulation mechanism when responding to C. neoformans.